Media and terrorism global perspectives - Freedman, Des; Thussu, Daya Kishan (SAGE, 2012)
Have the media contributed to exacerbating the political, cultural and religious divides within Western societies and the world at large? How can media be deployed to enrich, not inhibit, dialogue? To what extent has the media, in all its forms, questioned, celebrated or simply accepted the unleashing of a 'war on terror'? Media and Terrorism brings together leading scholars to explore how the world's media have influenced, and in turn, been influenced by terrorism and the war on terror in the aftermath of 9/11. Accessible and user-friendly with lively and current case studies, it is a perfect student text and an essential handbook on the dynamics of war and the media in a global context.